Comparative Legal Perspectives on Halal Tourism Regulations in Indonesia, Pakistan, and Nigeria - Hermawan Adinugraha, Hendri; Fikri, Muhammad Khoirul; Maulana, Asep Suraya; Sain, Zohaib Hassan; Lawal, Uthman Shehu (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The lack of harmonization in halal tourism regulations in Indonesia, Pakistan, and Nigeria has led to differences in standards, weak legal certainty, and inconsistent services that hinder the development of halal destinations. This study aims to analyse and compare the regulatory frameworks of halal tourism in Indonesia, Pakistan, and Nigeria, highlighting the differences in legal systems, institutional capacity, and their implications for the consistency of services and the development of the halal tourism industry. This research employs a qualitative method with a literature study approach, examining laws, government policies, institutional documents, and academic literature related to halal regulations. Data were analysed using content analysis techniques and comparative analysis to identify patterns of similarities, differences, and regulatory effectiveness across the three countries. The results of the study indicate that Indonesia has a more standardised halal regulatory framework, established through formal institutions such as BPJPH and MUI. In contrast, Pakistan adopts a market-driven approach due to the absence of formal regulations governing the halal tourism sector. Nigeria has fragmented rules due to its federal structure and dual legal system, resulting in varying standards of halal service across regions. The findings of this literature show that the legal system and the governance capacity of each country greatly influence the effectiveness of regulations. This research provides an understanding of the relationship between legal configuration and the efficacy of halal governance, offering a basis for regulatory harmonisation that strengthens the competitiveness of halal destinations. This study makes a new contribution by presenting a comprehensive comparative legal analysis of halal tourism regulations in three countries with distinct legal system characteristics, which have not been extensively discussed in previous studies. [Ketidakharmonisan regulasi pariwisata halal di Indonesia, Pakistan, dan Nigeria menimbulkan perbedaan standar, lemahnya kepastian hukum, dan inkonsistensi layanan yang menghambat pengembangan destinasi halal. Penelitian ini bertujuan menganalisis dan membandingkan kerangka regulasi pariwisata halal di Indonesia, Pakistan, dan Nigeria dengan menyoroti perbedaan sistem hukum, kapasitas kelembagaan, serta implikasinya terhadap konsistensi layanan dan pengembangan industri pariwisata halal. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi pustaka yang menelaah undang-undang, kebijakan pemerintah, dokumen kelembagaan, dan literatur akademik terkait regulasi halal. Data dianalisis melalui teknik analisis isi dan analisis komparatif untuk mengidentifikasi pola persamaan, perbedaan, dan efektivitas regulasi di ketiga negara. Hasil penelitian menunjukkan bahwa Indonesia memiliki kerangka regulasi halal yang lebih terstandardisasi melalui lembaga formal seperti BPJPH dan MUI, sedangkan Pakistan mengadopsi pendekatan market-driven akibat ketiadaan regulasi formal yang mengatur sektor pariwisata halal. Nigeria menampilkan regulasi yang terfragmentasi karena struktur federal dan dual legal system, sehingga standar layanan halal berbeda antar wilayah. Temuan pustaka ini menunjukkan bahwa efektivitas regulasi sangat dipengaruhi sistem hukum dan kapasitas tata kelola masing-masing negara. Penelitian ini memberikan pemahaman mengenai hubungan antara konfigurasi hukum dan efektivitas tata kelola halal, serta menawarkan dasar bagi harmonisasi regulasi dalam memperkuat daya saing destinasi halal. Penelitian ini memberikan kontribusi baru dengan menyajikan analisis hukum perbandingan yang komprehensif mengenai regulasi pariwisata halal di tiga negara dengan karakter sistem hukum yang berbeda, yang belum banyak dibahas dalam kajian sebelumnya.]